2001
DOI: 10.1080/03079450120066313
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell suppression by cyclosporin-A enhances infectious bursal disease virus infection in experimentally infected chickens

Abstract: In this study, the role of T lymphocytes was investigated in chickens experimentally infected with infectious bursal disease virus (IBDV). Chickens were treated with cyclosporin-A (CS-A), a selective T-cell suppressant drug, by the intramuscular route, starting 3 days before virus infection and every third day thereafter, and infectious bursal disease pathogenesis was compared in such T-cell suppressed and intact chickens using a vaccine strain; namely, Georgia and a field isolate of IBDV. Treatment of chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In particular, the short-lived response of the macrophage population is consistent with their role in removal of necrotic and apoptotic cell remnants, it has also been observed after infection with hypervirulent IBDV (34). The influx of T cells into the bursa is probably necessary for viral clearance (20,34) for higher titers of IBDV occur in chicks whose cell-mediated immune responses have been inhibited, for example by cyclosporin treatment (18). It has also been suggested that T cells inhibit the recovery of the bursal architecture (20), for a decline in number of CD4 ϩ and CD8 ϩ cells was associated with the presence of large reconstituted follicles.…”
Section: Figmentioning
confidence: 62%
See 1 more Smart Citation
“…In particular, the short-lived response of the macrophage population is consistent with their role in removal of necrotic and apoptotic cell remnants, it has also been observed after infection with hypervirulent IBDV (34). The influx of T cells into the bursa is probably necessary for viral clearance (20,34) for higher titers of IBDV occur in chicks whose cell-mediated immune responses have been inhibited, for example by cyclosporin treatment (18). It has also been suggested that T cells inhibit the recovery of the bursal architecture (20), for a decline in number of CD4 ϩ and CD8 ϩ cells was associated with the presence of large reconstituted follicles.…”
Section: Figmentioning
confidence: 62%
“…Ten 2-day-old Line 6 chicks were mockinfected using PBS. Four infected chicks were killed at 1, 2, 3, 4, 5, 6,7,10,14,18,20,27,34,40, and 54 days post-infection (dpi), and single non-infected controls were killed at various intervals for comparison. Samples of bursa, spleen, and thymus were removed for IHC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of numerous T cells suggests that cell-mediated immunity has a very important role to play in recovery from an infection with UK661. Poonia & Charan (2001) reported consistently higher titres of IBDV in chickens lacking a fully functional T-cell-mediated immune system. This increase in bursa T cells appears to be a consequence of migration and not an artefact due to the loss of B cells or the result of an expansion of resident T cells (Vervelde & Davison, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A rapid increase of CD4 + and CD8 + T cells in the bursal tissue during the first week after IBDV infection in chickens (Vervelde & Davidson, 1997;Poonia & Charan, 2001) can be involved in bursal tissue restoration. Bursal tissue restoration was found after inoculation of a vaccine strain (Geo) and a field isolate of IBDV (FIV) which were able to cause heterophils infiltration and lymphocytes necrosis along with vesicles formation in bursa follicles at early time post-infection (3 rd to 7 th dpi) (Poonia & Charan, 2001), and also after administration of Moulthrop hot strain of IBDV vaccine (Bolis et al, 2003) in chickens. It should be discussed that the presence of some birds with very low titers of humoral antibodies (B3 = 2/18 and B4 = 3/18) could have attenuated the extension of bursa damage caused by 2050/93 v.v.IBDV.…”
Section: Antibody Response In Vaccinated and Unvaccinated Chickens Afmentioning
confidence: 99%